Ex-Cit XR: Expert-elicitation and validation of Extended Reality visualisation and interaction techniques for disengaging and transitioning users from immersive virtual environments - Piumsomboon, Thammathip; Ong, Gavin; Urban , Cameron; Ens , Barrett; Topliss , Jack; Bai , Xiaoliang; Hoermann , Simon (Frontiers in Virtual Reality, 2022)
This research explores visualisation and interaction techniques to disengage users from immersive virtual environments (IVEs) and transition them back to the Augmented Reality mode in the real world. To gain a better understanding and novel ideas, we invited eleven Extended Reality (XR) experts to participate in an elicitation study to design such techniques for disengagement. From the elicitation study, we elicited a total of 132 techniques for four different scenarios of IVEs: Narrative-driven, Social-platform, Adventure Sandbox, and Fast-paced Battle experiences. Through extracted keywords and thematic analysis, we classified the elicited techniques into six categories of Activities, Breaks, Cues, Degradations, Notifications, and Virtual Agents. We shared our analyses on users' intrinsic motivation to engage in different experiences, subjective ratings of four design attributes in designing the disengagement techniques, Positive and Negative Affect Schedules, and user preference. In addition, we gave the design patterns found and illustrated the exemplary user cases of Ex-Cit XR. Finally, we conducted an online survey to preliminarily validate our design recommendations. We proposed the SPINED behavioural manipulation spectrum for XR disengagement to guide how the systems can strategically escalate to disengage users from an IVE.